Safety, specificity and immunogenicity of a PrP(Sc)-specific prion vaccine based on the YYR disease specific epitope - Taschuk, Ryan (Prion, 2014)
Prions are a novel form of infectivity based on the misfolding of a self-protein (PrP(C)) into a pathological, infectious isomer (PrP(Sc)). The current uncontrolled spread of chronic wasting disease in cervids, coupled with the demonstrated zoonotic nature of select livestock prion diseases, highlights the urgent need for disease management tools. While there is proof-of-principle evidence for a prion vaccine, these efforts are complicated by the challenges and risks associated with induction of immune responses to a self-protein. Our priority is to develop a PrP(Sc)-specific prion vaccine based on epitopes that are uniquely exposed upon misfolding. These disease specific epitopes (DSEs) have the potential to enable specific targeting of the pathological species through immunotherapy. Here we review outcomes of the translation of a prion DSE into a PrP(Sc)-specific vaccine based on the criteria of immunogenicity, safety and specificity.